1995
DOI: 10.1016/0735-1097(94)00462-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and lesion morphologic determinants of coronary angioplasty success and complications: Current experience

Abstract: The previously proposed classification schemes are outdated and need to be changed for application in current angioplasty practice. Analyzing specific lesion morphologic characteristics rather than applying a simple lesion classification score when evaluating angioplasty outcome may be more useful because it provides a more precise profile of the lesion and allows better patient stratification and selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
97
1
4

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(109 citation statements)
references
References 51 publications
4
97
1
4
Order By: Relevance
“…1,4,5,13,16,17) The results of this study extend our previous observations, demonstrating the predictive value of measuring plasma levels of IL-8 for early complications after coronary interventions. Buffon, et al reported that the preprocedural CRP level is a powerful predictor of both early and late outcome in patients undergoing single vessel PTCA.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…1,4,5,13,16,17) The results of this study extend our previous observations, demonstrating the predictive value of measuring plasma levels of IL-8 for early complications after coronary interventions. Buffon, et al reported that the preprocedural CRP level is a powerful predictor of both early and late outcome in patients undergoing single vessel PTCA.…”
Section: Discussionsupporting
confidence: 78%
“…4,5) Our previous study revealed that there were dynamic changes of plasma IL-8 level and a correlation between CRP and the expression of β 2 -integrin Mac-1 (CD11b/CD18) on monocytes in patients undergoing PCI. 6) Therefore, we investigated the prognostic value of peri-procedural plasma levels of IL-8, serum levels of CRP, and the expression of CD11b/CD18 on neutrophils in patients with early complications following PCI.…”
mentioning
confidence: 99%
“…Massive calcifications of the coronary arteries constitute a major obstacle to the success of coronary angioplasty [10,11]. They can prevent the introduction of a balloon catheter and/or its expansion, can cause an injury to the polymer and/or drug layer of the coated stents and may prevent the delivery and full expansion of the stent.…”
Section: Discussionmentioning
confidence: 99%
“…В свою очередь, К. Tan и соавт. отметили, что поражения типа С по-разному предопределяют исход вмешательства, несмо-тря на то, что объединены в одну и ту же группу [13]. В ходе исследования было установлено, что непосредственный успех ЧКВ (57-88%) и частота острой окклюзии КА (3-16%), вызванная тромбозом или диссекцией, ассоциировались с определенными характеристиками (протяженность пора-жения, кальциноз и степень стенозирования 80-99%) [14].…”
unclassified